Intimate partner violence perpetration, standard and gendered STI/HIV risk behaviour, and STI/HIV diagnosis among a clinic-based sample of men. Issue 7 (21st July 2009) - Decker, M R; Seage, G R; Hemenway, D; Gupta, J; Raj, A; Silverman, J G
Abstract : Background: The estimated one in three women worldwide victimised by intimate partner violence (IPV) consistently demonstrate elevated STI/HIV prevalence, with their abusive male partners' risky sexual behaviours and subsequent infection increasingly implicated. To date, little empirical data exist to characterise the nature of men's sexual risk as it relates to both their violence perpetration, and STI/HIV infection. Methods: Data from a cross-sectional survey of men ages 18–35 recruited from three community-based health clinics in an urban metropolitan area of the northeastern US (n = 1585) were analysed to estimate the prevalence of IPV perpetration and associations of such violent behaviour with both standard (eg, anal sex, injection drug use) and gendered (eg, coercive condom practices, sexual infidelity, transactional sex with a female partner) forms of sexual-risk behaviour, and self-reported STI/HIV diagnosis. Results: Approximately one-third of participants (32.7%) reported perpetrating physical or sexual violence against a female intimate partner in their lifetime; one in eight (12.4%) participants self-reported a history of STI/HIV diagnosis. Men's IPV perpetration was associated with both standard and gendered STI/HIV risk behaviours, and to STI/HIV diagnosis (OR 4.85, 95% CI 3.54 to 6.66). The association of men's IPV perpetration with STI/HIV diagnosis was partially attenuated (adjusted odds ratio (AOR) 2.55, 95% CI 1.77 to 3.67) in the multivariate model, and a subset of gendered sexual-risk behaviours were found to be independently associated with STI/HIV diagnosis—for example, coercive condom practices (AOR 1.67, 95% CI 1.04 to 2.69), sexual infidelity (AOR 2.46, 95% CI 1.65 to 3.68), and transactional sex with a female partner (AOR 2.03, 95% CI 1.36 to 3.04). Conclusions: Men's perpetration of physical and sexual violence against intimate partners is common among this population. Abusive men are at increased risk for STI/HIV, with gendered forms of sexual-risk behaviour partially responsible for this association. Thus, such men likely pose an elevated infection risk to their female partners. Findings indicate the need for interwoven sexual health promotion and violence prevention efforts targeted to men; critical to such efforts may be reduction in gendered sexual-risk behaviours and modification of norms of masculinity that likely promote both sexual risk and violence